A root-knot nematode effector manipulates the rhizosphere microbiome for establishing parasitism relationship with hosts - Liu, Rui; Chen, Mengfei; Liu, Boliang; Huang, Kaiwei; Mao, Zhenchuan; Li, Huixia; Zhao, Jianlong (Frontiers in Microbiology, 2023)
Root-knot nematode (RKN; Meloidogyne spp.) is one of the most infamous soilborne plant diseases, causing severe crop losses every year. Effector proteins secreted by RKNs play crucial roles during plant-nematode interaction. However, little is known about whether RKN effector proteins can impact the rhizosphere microbial environment. In this study, we investigated the rhizosphere microbiome community of MiMIF-2 (a plant immunity modulating effector) transgenic Arabidopsis thaliana with or without nematode infection using Illumina high throughput sequencing analysis.Results showed that the bacterial species richness index increased, while fungi species richness index decreased in M. incognita infected MiMIF-2 transgenic A. thaliana plants. The genera relative abundance of Clitopilus, Komagataeibacter, Lactobacillus, Prevotella, Moritella, Vibrio, Escherichia-Shigella, and Pseudomonas were reduced in MiMIF-2 transgenic A. thaliana plants compared to wild-type, but significantly increased after inoculation with M. incognita. COG function classification analysis revealed a decrease in the relative abundance of defense mechanisms, secondary metabolite biosynthesis, transport, and nematode infection catabolism-related functions in MiMIF-2 lines compared to the wild type. These differences may be the reason for the increased susceptibility of MiMIF-2 transgenic A. thaliana to nematode infection.Our results provide a new insight on RKN effector proteins, their association with microbial community, host and plant pathogens, and will lead to explore new innovative ideas for future biological control of RKNs.